Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz